POTENSI PEMANFAATAN YOUTUBE DALAM PEMBELAJARAN MATEMATIKA - Fira Nur Setiyana; Anggun Badu Kusuma (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
Information technology has a very important role in learning. YouTube is used as a teaching media to help overcome the difficulties of teaching and learning activities during the Covid-19 pandemic period. Providing sources of information in the form of materials and other additional information is very useful so students can understand the material optimally. The purpose of writing this article is to provide information so that it can be used as a source of readers about the potential for youtube utilization in mathematics learning. This research is a literature review that examines ideas, opinions, or findings contained in online articles and journals related to titles and research content so that it provides theoretical information. The results of this study concluded that the potential for youtube utilization in mathematics learning has a positive effect in increasing student learning interest and can motivate students to learn because information on YouTube is very diverse so that it will be useful in the current learning conditions.